ChemInform Abstract: Preparation, Nonlinear Optical Properties, and Theoretical Analysis of the Non‐Centrosymmetric Bismuth Oxyfluoride, Bi7F11O5. Issue 10 (February 2016) - Hu, Wei; Shan, Pai; Sun, Tongqing; Liu, Hongde; Zhang, Jianming; Liu, Xuanwen; Kong, Yongfa; Xu, Jingjun
Abstract: The title compound is hydrothermally prepared from an aqueous mixture of Bi(NO3 )3 and ZnF2 (autoclave, 200 °C, 72 h, 90% yield).